Sic transit gloria mundi? Thoughts on Ataturkism - Siska Katalin (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. The Ataturkism actually occurred after the death of Mustafa Kemal Atatürk. The criticism of his ideology often served as a pretext, where Atatürk's political programs were presented along the own concept of the interpreter. The cult of Atatürk is not at all unprecedented in the history of Hungarian politics. Between the World Wars there was not any foreign politicians who had such a unanimous positive opinion as Mustafa Kemal Atatürk had. For different reasons among communists and Social Democrats Atatürk beyond disputes had held positive personality in the public opinion. The reason for the general recognition was undoubtedly his successful modernization policy, as well as his balanced foreign policy (including the agreement with Soviet Russia), a successful attack against Versailles Peace Treaty, and his social policy. There was consensus among the Hungarian (mis) judgers that he was a modernizing dictator who followed a balanced foreign policy in an era in which Hungary was unable to do so. The uncritical follow of the Atatürk example is only suggested by the Magyar Nemzet who visioned Atatürk as a racial politician. In my study I focus on the essence of his flexible policy, which served as a model that could be easily used not only in the Middle East, but in the '30s Hungarian public policy as well.

Atatürkizmusról gyakorlatilag Mustafa Kemál Atatürk halála után beszélhetünk. Ideológiájának kritikája gyakran ürügyként szolgált, ahol Atatürk politikai programjait az interpretáló a saját céljainak megfelelően mutatta be. Atatürk kultusza a magyar történelemben sem példa nélküli. A két világháború között nem volt olyan politikus, aki ideológiájának annyi értelmezése lett volna, mint Atatürknek. A kommunisták és a szociáldemokraták különböző szempontok szerint emelték példává, emellett Atatürköt a közvélemény is vitán felüli pozitív személyiségnek tekintette. Az általános elismerés oka kétségtelenül sikeres modernizációs politikája, valamint kiegyensúlyozott külpolitikája (beleértve a Szovjetunióval kötött megállapodást), a Versailles-i békeszerződés sikeres megtámadása és szociálpolitikája volt. Hazai értelmezői (és félreértelmezői) között is egyetértés volt abban, hogy modernizáló diktátor volt, aki kiegyensúlyozott külpolitikát követett egy olyan korszakban, amikor Magyarország erre képtelen volt. Tanulmányomban a rugalmas politikájának lényegére összpontosítottam, amely könnyen modellként szolgált nemcsak a Közel-Keleten, hanem a harmincas évek magyarországi közpolitikájának is.

Резюме. Фактично про явище ататюркізму можемо говорити з часу смерті Мустафи Кемаля Ататюрка. Критика його ідеології часто служила підставою, щоб відповідний інтерпретатор представляв політичну програму Ататюрка відповідно до своїх цілей. Культ Ататюрка був характерним і для історії Угорщини. У період між двома світовими війнами не було такого політика, ідеологія якого мала б стільки тлумачень, як в Ататюрка. У різних сферах його ставили за приклад як комуністи, так і соціал-демократи, крім цього, Ататюрк був безперечно позитивною постаттю і для громадської думки. Причиною його загального визнання, без сумніву, була успішна політика модернізації, а також врівноважена зовнішня політика (включаючи укладення угоди з Радянським Союзом), успішна критика Версальського мирного договору і соціальна політика. Численні угорські інтерпретатори діяльності цього політика погоджувалися в тому, що це був модерний диктатор, який здійснював виважену зовнішню політику в епоху, коли Угорщина була на це нездатна. У статті акцентовано увагу на суті гнучкої політики Ататюрка, яка могла послужити моделлю не тільки для Близького Сходу, але й для Угорщини 30-х років ХХ ст.
Sic transit gloria mundi? Gondolatok az atatürkizmusról
«Sic transit gloria mundi?» Роздуми про ататюркізм
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008905
Keywords: Kemalism; political principles; Republic of Turkey; Mustafa Kemal Atatürk; Republic of Hungary; nacionalism